Glare-free high beam optimization based on country road traffic simulation. (October 2019) - Kobbert, J; Kosmas, K; Khanh, TQ
Throughout recent years, more and more vehicles in all classes have been equipped with glare-free high beam lighting. Series production started in 2012 with mechanical systems of near infinite resolution but with the constraint of cutting out only one single traffic element per situation. Today's glare-free high beam systems use discrete and individually addressable Light Emitting Diods (LEDs) in order to achieve even more functionality. This includes, for example, cutting out two or more cars from the light distribution, while at the same time being more energy efficient and without any mechanical movement. This paper presents a method to further increase the efficiency of glare-free high beam systems with discrete light sources based on country road traffic simulations. Especially for low resolution glare-free high beam systems, a large improvement in performance and road illumination can be achieved using the proposed method. Furthermore, the simulation is used to investigate the necessary system response time to successfully mask out traffic in different situations.